2009
DOI: 10.1111/j.1524-4741.2009.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Breast Cancer through Population-Based Mammographic Screening in Asian Women: A Comparison Study between Screen-Detected and Symptomatic Breast Cancers

Abstract: The first nation-wide mammographic screening program in Asia, BreastScreen Singapore (BSS), was launched in Singapore in January 2002. This study compared the presentation and results of screen-detected breast cancers with symptomatic breast cancers in two affiliated high-volume institutions, one of which was an assessment centre for BSS. The medical records of patients diagnosed with primary breast cancer at the Department of General Surgery, Singapore General Hospital and the Department of Surgical Oncology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
3
34
2
Order By: Relevance
“…This is consistent with the findings of similar studies in other countries, such as Singapore. 6 This study may provide evidence that supports the benefits of regular screening to detect breast cancer lesions at an early stage in Hong Kong women. This will facilitate less invasive surgery and a possibly better overall clinical outcome.…”
Section: Discussionsupporting
confidence: 56%
“…This is consistent with the findings of similar studies in other countries, such as Singapore. 6 This study may provide evidence that supports the benefits of regular screening to detect breast cancer lesions at an early stage in Hong Kong women. This will facilitate less invasive surgery and a possibly better overall clinical outcome.…”
Section: Discussionsupporting
confidence: 56%
“…The majority of the patients in the study cohort were Chinese, and expected to have similar physical attributes in terms of breast tissue volume as Chinese women elsewhere. Still, BCT rates in the study cohort are higher than in other Chinese-dominant countries (Chuwa et al, 2009;Yau et al, 2009;Yip et al, 2009;Chang et al, 2011;Wang et al, 2011) and are similar to, if not also higher than, those reported in Western countries (Lee et al, 2009;McGuire et al, 2009;Garcia-Etienne et al, 2012;Agarwal et al, 2014). Hence, the issue of smaller breast tissue volume and its impact on BCT rates needs further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…The obtained results showed that the IABC incidence rates reduced from 2004 to 2006, possibly because of the annual increase in early screening and detection [28,29] . However, the proportion of capecitabine or trastuzumab administration has increased in the recent years, indicating that higher patients with IABC are receiving ATT and ATC.…”
Section: Discussionmentioning
confidence: 78%